2016
DOI: 10.1074/jbc.m115.703066
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Regulates the Activity of Pyruvate Kinase M2

Abstract: Parkin, a ubiquitin E3 ligase, is mutated in most cases of autosomal recessive early onset Parkinson disease. It was discovered that Parkin is also mutated in glioblastoma and other human malignancies and that it inhibits tumor cell growth. Here, we identified pyruvate kinase M2 (PKM2) as a unique substrate for parkin through biochemical purification. We found that parkin interacts with PKM2 both in vitro and in vivo, and this interaction dramatically increases during glucose starvation. Ubiquitylation of PKM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(68 citation statements)
references
References 51 publications
2
65
1
Order By: Relevance
“…PKM plays an important role in the maintenance of different forms of persistent long-term synaptic plasticity [51]. It has been reported that pyruvate kinase M is the substrate of Parkin, a ubiquitin E3 ligase mutated in autosomal recessive, early onset Parkinson’s disease [52]. We detected higher levels (2.2-fold) of PKM in AD patients using five peptides for targeted analysis (Figure 3E, F).…”
Section: Resultsmentioning
confidence: 64%
“…PKM plays an important role in the maintenance of different forms of persistent long-term synaptic plasticity [51]. It has been reported that pyruvate kinase M is the substrate of Parkin, a ubiquitin E3 ligase mutated in autosomal recessive, early onset Parkinson’s disease [52]. We detected higher levels (2.2-fold) of PKM in AD patients using five peptides for targeted analysis (Figure 3E, F).…”
Section: Resultsmentioning
confidence: 64%
“…and ubiquitylating pyruvate kinase M2 (PKM2) (162), decreasing its activity and glucose metabolic rate (131). Alterations in ER-mitochondria contact sites: the case of AD.…”
Section: Possible Mechanism Of Oxphos Deficiency In Neurodegenerativementioning
confidence: 99%
“…The interaction between PKM2 and Parkin was favored by glucose starvation. Parkin silencing rescued the activity of PK and supported tumor growth ( 65 ). In addition, the laforin/malin E3-ubiquitin ligase complex, which is mutated in neurodegenerative Lafora disease, interacts and polyubiquitinates both M-isoforms of PK.…”
Section: Ubiquitination and Sumoylationmentioning
confidence: 99%